Participation in the construction of a local public good with indivisibilities: An application to watershed development in Ethiopia - Gaspart, F.; Jabbar, M.A.; Melard, C.; Platteau, J.P. (1998)
The logic of voluntary contributions to an indivisible public good is studied, firstly in a simple game-theoretical framework, then in an empirical investigation of a case of watershed development in the Ethiopian Highlands. The former approach emphasises the difference between the problem under attention and the classical representation of public good provision, i.e., the Prisoner's Dilemma. The latter approach emphasises the joint role of leadership and of private interests as key determinants of individual contributions, thereby illustrating the game-theoretical model and providing well-founded guidelines for similar collective actions.